Penurunan Kadar IL-1β Makrofag Terpapar Agregat Bakteri Actinomycetemcomitans setelah Pemberian Minyak Atsiri Temu Putih - Juni Handajani; Siti Fatimah; Ristini Asih; Antinah Latif (Majalah Kedokteran Gigi Indonesia, 2015)
IL-1β level of macrophage exposed to A. actinomycetemomitans decreases after administration Curcuma Zedoaria volatile oil. Activation of interleukin-1β (IL-1β) is a key regulator of the inflammatory response. Macrophage is a phagocytic mononuclear cell that plays an important role in innate and adaptive immune response. The cytokine secreted by macrophages in response to pathogen are IL-1, IL-6, IL-12, TNF-α and chemokine. Curcuma zedoaria volatile oil may have anti inflammation effect. The aim of this study was to investigate IL-1β level of macrophage exposed to A. actinomycetemcomitans after administration Curcuma zedoaria volatile oil. The subjects were 10 male Wistar rats, which divided into two groups (treatment and control), each group 5 rats. In the treatment group, 30,6 μl/ml Curcuma zedoaria volatile oil was administered per oral for 14 days and the control group used aquabidest. In the 7th days, 100 μl A. actinomycetemcomitans in CMC 2% were applied on the anterior gingival mandible for 7 days. Rats were anesthetized in the 15th days then macrophage was collected from peritoneal. Interleukin-1β level of macrophage was measured using ELISA kit (R&D Systems, USA). Data were analyzed using t-test. The result showed IL-1β level decreased after treatment. The comparison between treatment and control was significant difference (p<0.05). It can be concluded that Curcuma zedoaria volatile oil may have anti inflammation effect through reducing the IL-1β level of macrophage.